KAJIAN PEMANFAATAN KEBUN BINATANG MINI JANTHO SEBAGAI PENUNJANG PEMBELAJARAN BIOLOGI - Abdullah Abdullah (Universitas Syiah Kuala, 2010)
The research about animal species of mini zoo of Jantho, Aceh Besar subdistric had been conducted from 21 to 24 January 2010. This research purpose was to investigate animal species in mini zoo of Jantho as biology learning support. Expedition was chosen as a method in this research by direct observation to the location. The result showed that there are 11 species animals consisting of eagle (Accipiter fasciatur), bintarung (Arctictis bintarung), red cat (Felis badia), landak (Hystrix brachura), honey bear (Hylarcstors malayanus), crocodile (Crocodiles porosus), rusa sambar (Cervus unicolor), mawas (Pongo abelli), beruk (Macaca nemestrina), ular sanca (Python reticulates), kukang (Nycticebus caucang). The existence of mini zoo and the animals inside could support biology learning process.